Changes in the distribution and predictive modeling of downy brome (Bromus tectorum L.) at high elevations - Bromberg, James, author; Brown, Cynthia Stokes, advisor; Meiman, Paul J., committee member; Stohlgren, Thomas J., committee member (Colorado State University. Libraries, 2010)
Downy brome (Bromus tectorum L.), an invasive winter annual grass, may be increasing in extent and abundance at high elevations in the western United States. This may pose a threat to high elevation plant communities and resources. Anecdotal information suggested this range expansion in the Rocky Mountains, but data to confirm it was limited. The initial goal of my project was to examine whether downy brome was increasing at elevations above its typical range of up to 2440 m by resampling prior field studies. I further expanded my goals to make predictions about future range expansion using Maxent, a habitat matching model. I also evaluated how well the model predicted the future distribution of downy brome through additional field sampling. Two vegetation surveys in Rocky Mountain National Park (RMNP) conducted in 1993 and 1999 were resampled in 2007. Although these surveys were not initially established to examine downy brome specifically, they were useful in tracking changes in downy brome presence, abundance, and distribution. Statistical analyses were used to examine presence and abundance of downy brome, while the predictive modeling explored the potential distribution throughout RMNP. Stratified random sampling throughout RMNP in 2008 was used to validate how well the model predicted the distribution of downy brome. Results of the studies confirm suspicions that downy brome is spreading within RMNP. Analyses of the field sampling indicate that expansion of downy brome is likely occurring both in abundance and frequency at elevations ranging from 2470 m to 3080 m. Predictive modeling also indicates that further range expansion is likely within RMNP as new incidence of downy brome tend to be found within areas with a high predicted probability of occurrence. The stratified random points sampled throughout RMNP confirmed that the model performed well over a larger spatial scale despite the limited extent of the initial samples. Because downy brome appears to be increasing, managers of high elevation lands may need to consider taking a more active role in preventing further spread. The accurate model predictions made with a relatively small sample size indicate that Maxent can be an extremely useful tool for land managers who have limited time and resources. Predictive models, however, are just one of many types of information to be considered in making management decisions and should be used in conjunction with other resources.
Department Head: N. LeRoy Poff.